The social foundations of German unification, 1858-1871. Ideas and institutions - Hamerow, Theodore S. (Princeton, New Jersey : Princeton University Press, 1969)
The diplomatic and political events leading to the establishment of the German Empire have been studied extensively, but the social matrix of civic activity has been sadly neglected. Professor Hamerow fills this gap by dealing first with the development of the economy and the community under the influence of industrialization. He then considers the ideologies of the era and the groups supporting them: liberalism and the middle class; conservatism and the outlook of the old order; socialism and the emerging industrial working class. The final section of his book is on the structure of politics.
Cover -- Contents -- Alphabetical List of Cited Works.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed February 16, 2015).
eBooks on EBSCOhost
Keywords: Bismarck, Otto, -- Fürst von, -- 1815-1898.; Bismarck, Otto, -- Fürst von, -- 1815-1898; Germany -- Politics and government -- 1848-1870.; Germany -- Economic conditions -- 19th century; Germany -- Social conditions; Allemagne -- Politique et gouvernement -- 1848-1870.; Allemagne -- Conditions économiques -- 19e siècle.; Allemagne -- Conditions sociales; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Economic history; Politics and government; Social conditions; Germany; 1800-1899